Assessment protocols in orofacial motricity: a systematic review (Research, Society and Development, 2022)
Objective: To systematically review the assessment protocols in orofacial motricity. Method: The research was carried out in PubMed, LILACS and SciELO databases with protocols published in the last 15 years. The descriptors used were: evaluation; stomatognathic system; breathing; chewing; Deglutition; speech therapy and its similar in English. This systematic review was conducted according to the PRISMA instrument guidelines and analyzed for its quality by the STARD15 instrument, with high agreement among the judges. Results: Twelve studies were eligible, most of them developed in Brazil and with a population between six months and 55 years of age and with different clinical and conceptual objectives. The most described protocols were MBGR and AMIOFE, which have good sensitivity and specificity. No meta-analysis was performed. Conclusion: The present study systematically reviewed the assessment protocols in orofacial motricity, and found methodological discrepancies in relation to the sample size of assessment instruments used for the diagnosis of orofacial myofunctional disorders.